2017
DOI: 10.1038/srep46572
|View full text |Cite
|
Sign up to set email alerts
|

Meta-signature LncRNAs serve as novel biomarkers for colorectal cancer: integrated bioinformatics analysis, experimental validation and diagnostic evaluation

Abstract: The aim of this study is to explore the differentially expressed lncRNAs, which may have potential biological function and diagnostic value in colorectal cancer (CRC). Through integrated data mining, we finally identified nine differentially expressed lncRNAs and their potential mRNA targets. After a series of bioinformatics analyses, we screened significant pathways and GO terms that are related to the up-regulated and down-regulated transcripts respectively. Meanwhile, the nine lncRNAs were validated in 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 56 publications
(59 reference statements)
1
36
1
1
Order By: Relevance
“…This result suggested that high BLACAT1 expression could be regarded as a specific prognostic factor In UCEC. This result was inconsistent with the previous studies that reported the BLACAT1 could act as a prognostic factor in GC, BLC and CRC [ 19 – 21 ]. One possible reason was that normal tissues were fewer than cancer tissues in TCGA database.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This result suggested that high BLACAT1 expression could be regarded as a specific prognostic factor In UCEC. This result was inconsistent with the previous studies that reported the BLACAT1 could act as a prognostic factor in GC, BLC and CRC [ 19 – 21 ]. One possible reason was that normal tissues were fewer than cancer tissues in TCGA database.…”
Section: Resultscontrasting
confidence: 99%
“…These 12 different types of cancer included: HCC, lung cancer (LC), breast cancer (BC), ovarian cancer (OC), EMC, cervical cancer (CC), PC, gastric cancer (GC), esophagus cancer (EC), thyroid cancer (TC), BLC and nasopharynx cancer (NPC). For the diagnostic value of serum BLACAT1 in CRC was reported in our previous article, the CRC was not included in present study [ 21 ]. According to the qRT-PCR confirmation results, serum BLACAT1 was performed well in distinguishing cancer from healthy subjects in these 12 types of cancer, which was not able to distinguish cancer from benign lesions in BC, OC, PC and NPC (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression microarrays have been widely applied for the diagnosis of various cancers ( 20 , 21 ). An important application of microarray experiments is the analysis of differentially expressed miRNAs or mRNAs between normal and tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84][85][86][87]92 Furthermore, a recent study, after a series of bioinformatic analyses, screening important pathways and GO terms that were related to upregulated and downregulated transcripts, noted that lncRNA BLACAT1 and four downregulated lncRNAs including LOC344887, LINC00675, DPP10-AS1, and HAGLR are all biomarkers for diagnosis of CRC. 114 In this regard, studies revealed that exosomal BCAR4 lncRNA is downregulated in the serum of patients with colon adenoma compared with normal subjects. In addition, the combination of two mRNAs, KRTAP5-4, and MAGEA, with this lncRNA provided a suitable panel for diagnosis of CRC (Table 3).…”
Section: Of Crcmentioning
confidence: 99%